Efektivitas dan Kontribusi Pajak Perhotelan terhadap Pendapatan Asli Daerah Kabupaten Indragiri Hulu Tahun 2013-2019 - Aris Triyono; Albetris Albetris; Sumantri Sumantri; Etty Siswati (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The research was conducted at the Regional Revenue Agency of Indragiri Hulu Regency. The purpose of this study is to analyze and find out how much effect the Effectiveness and contribution of Hospitality tax to the Original Revenue of Indragiri Hulu Regency both simultaneously and partially with the research period is 5 years from 2013 to 2019. This type of research is quantitative research using secondary data. The Research Method used is quantitative method with multiple linear regression equations, while the Equation is Y = 45712635725,406 - 19524572,193 X1 + 25765555,817 X2. From the results of data processing SPSS is known simultaneously known if the effectiveness and contribution of hospitality tax receipts have a significant effect on the original revenue of the region. From the SPSS results, it is known that there is partially no significant influence between effectiveness to the original revenue of the region and partially there is a significant influence between the contribution of hotel tax receipts partially to the original revenue of the region.